Má carpintaria: por uma arquitetura menor - Adriano Mattos Correa (2014)
Constructive practice of "minor" value tell us about possibilities for the edification of other and different folds in the production of what is named as contemporary architecture. In a territorial context, increasingly urbanized and dominated by an order based on a uniform management, hygienic, policed and institutional our social, economic and cultural existences, the experience of a "bad carpentry" hosts know each other, share and investigates other modes for the formation and practice of an architect. A "minor" architecture announces presence of relationships shared by guys named, inhabitants of natural contexts, and willing to experiment so accomplice and singular, in the cracks of the "biggest" architectural domain, other modes of living and build our space mediations.